Opinions of contemporary Muslim jurists on the registration of marriages - Mahmud , Mek Wok (International Islamic University Malaysia, 2011)

(untitled)
Registration of marriages is one of the debatable issues among contemporary Muslim scholars. Considering the fact that it was not implemented during the Prophet’s (s.a.w) time, many scholars discuss the validity of its practice as one of Shari‘ah requirements to recognize a marriage contract. There is a need to critically analyze the opinions of contemporary Muslim schoars on the registration of marriage as a requirement for a marriage contract to be recognized and officially authenticated, as currently practiced in many Muslim countries. Adequate attention is needed to be paid to the issue of the Sharī‘ah status of marriage registration, as it has no basis among the Sharī‘ah requirements for a valid marriage contract. This paper takes into consideration ten principles of Islamic jurisprudence such as al-Qiyās, Sadd al-Dharā’i‘, al-IstiÍsān, Maqāsid al-sharī‘ah and as-Siyāsah al-Shar‘iyyah to prove that the registration of marriage cannot be regarded as alien to Islamic law.